Edukasi Penggunaan Suplemen Selama Pandemi Covid-19 pada Kader Kesehatan di Wilayah Kerja Puskesmas Karangan Kabupaten Trenggalek: Education on the Use of Supplements During the Covid-19 Pandemic for Health Cadres in the Work Area of the Karangan Health Center Trenggalek Regency - Widyaningrum, Esti Ambar; Kurniawati, Evi; Lestari, Tri Puji; Pertiwi, Krisna Kharisma (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Several ways can be used to boost the immune system, one of which is by using supplements that can be obtained through a doctor's recommendation or pharmacist consultation. Low immunity in humans will make it easy to be exposed to diseases or viruses, including quickly exposure to Covid-19. This is why many people take supplements: they think the amount of minerals and vitamins they get from their food is insufficient to keep their immune system healthy. One of the considerations for taking supplements is knowledge of their benefits. Even though supplements are not drugs, their use must also be rational. Individuals with adequate knowledge, especially about supplements, will tend to choose and use supplements according to conditions and benefits for the body. To find out the effectiveness of counseling in increasing knowledge of the use of supplements to increase body immunity during the Covid-19 pandemic for health cadres in the Karangan Health Center, Trenggalek Regency working area. This community service is conducted through lectures and question-and-answer method counseling. The number of participants in this activity was 33 health workers in the work area of the Karangan Health Center, Trenggalek Regency. Results: There was an increase in knowledge of the use of immunity-boosting supplements in health cadres in the work area of the Karangan Health Center, Trenggalek Regency, from the majority of sufficient knowledge (pre-test) to good (post-test). Education on using supplements can increase the knowledge of health cadres in the work area of the Karangan Health Center.